Silk-engineered bioactive nanoparticles for targeted alleviation of acute inflammatory disease via macrophage reprogramming - Renfeng Liu; Erkang Zhao; Yejing Wang; Hua Zuo; Lanlan Li; Qingyou Xia; Huawei He (Journal of Nanobiotechnology)
Abstract Significant progress has been made in the development of potential therapies for diseases associated with inflammation and oxidative stress. Nevertheless, the availability of effective clinical treatments remains limited. Herein, we introduce a novel silk-based bioactive material, TPSF, developed by sequentially conjugating Tempol and phenylboronic acid pinacol ester to silk fibroin. This innovative reactive oxygen species (ROS) scavenging material not only effectively eliminates free radicals and hydrogen peroxide but also readily self-assembles into nanoparticle forms (TPSN). In vitro experiments have demonstrated that TPSN exhibits significant anti-inflammatory activities and cytoprotective effects against ROS-mediated damage. Consistently, in murine models of acute lung and kidney injury, TPSN outperforms the small-molecule antioxidant NAC, exhibiting superior therapeutic efficacy. Mechanistically, TPSN has the capability to reprogram M1-like macrophages toward an M2-like state. Importantly, biocompatibility assays confirm that TPSN has good safety profiles. Consequently, TPSN, characterized by its favorable protective effects and excellent biocompatibility, exhibits considerable promise as a therapeutic intervention for inflammation-related diseases. This innovative strategy, which incorporates multifunctional antioxidant components into the silk fibroin matrix, effectively addresses oxidative stress and acute inflammation. Furthermore, it highlights the potential of modified silk fibroin materials in the management and mitigation of inflammation-led tissue damage.